(untitled) (Research, Society and Development, 2023)
For several decades, the Poxvirus family has been a threat to several continents, causing damage to the European population during the Middle Ages. Currently, some emerging species are becoming endemic, such as the scenario of monkeypox in the Brazilian health service, requiring efforts to eradicate them. The work in question seeks to highlight the difficulties of epidemiological surveillance in the sense of early diagnosis of virus carriers. The literary analysis of the most recent articles and magazines on the subject was used as a methodology, seeking to correlate the difficulties encountered for its diagnosis. Thus, it was possible to notice a threat to current public health, given the lack of knowledge about monkeypox disease, as well as the neglect and fake news disseminated by Brazilian society. Therefore, public measures need to be elaborated so that the constraints of this late diagnosis are minimized in the Brazilian territory, aiming to evaluate the social, sexual, economic and class issues that surround Monkeypox.